ANALISIS DETERMINAN KETIMPANGAN PENDAPATAN ANTAR PROVINSI DI PULAU SUMATRA (STUDI KOMPARATIF PROVINSI KEPULAUAN RIAU DAN PROVINSI KEPULAUAN BANGKA BELITUNG) - Yoga Fadhlih Sarwono; Zamzami; Candra Mustika (PT. Saha Kreasi Indonesia, 2025)
This study, entitled “Analysis of the Determinants of Income Inequality Between Provinces in Sumatra Island (A Comparative Study of Riau Islands Province and Bangka Belitung Islands Province)”, aims to analyze and compare the factors influencing income inequality among regencies/cities in Riau Islands Province and Bangka Belitung Islands Province during the 2019–2024 period. The variables used include economic growth, average years of schooling, open unemployment rate (OUR), and road infrastructure, with the Gini ratio as the indicator of income inequality. This study employs a quantitative method using panel data regression analysis. The results show that in Riau Islands Province, the economic growth variable has a negative and significant effect on income inequality, while education and unemployment have positive and significant effects. On the other hand, in Bangka Belitung Islands Province, road infrastructure and economic growth negatively affect income inequality, although with different levels of significance. This comparison indicates that economic growth and infrastructure equity are more effective in reducing income inequality in Bangka Belitung than in Riau Islands Province.